2007
DOI: 10.1016/s1808-8694(15)30108-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Middle Meatus in Chronic Rhinosinusitis

Abstract: The microbiology of the middle meatus is similar in CRS patients and healthy individuals. Despite this, there was an important difference between the WBC count in these two groups, which helps to distinguish an infective from a saprophitic microorganism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
4
20
0
1
Order By: Relevance
“…On the whole, the organisms identified in this study were very similar to those identified in previous culture-based investigations into the microflora of CRS patients. Thus, staphylococci (both S. aureus and coagulase-negative staphylococci) and α-haemolytic streptococci were the most commonly isolated organisms, in agreement with published reports [18], [20]–[22]. Corynebacteria were isolated from seven CRS patients, and several potential pathogens were identified, including M. catarrhalis , Neissseria spp.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the whole, the organisms identified in this study were very similar to those identified in previous culture-based investigations into the microflora of CRS patients. Thus, staphylococci (both S. aureus and coagulase-negative staphylococci) and α-haemolytic streptococci were the most commonly isolated organisms, in agreement with published reports [18], [20]–[22]. Corynebacteria were isolated from seven CRS patients, and several potential pathogens were identified, including M. catarrhalis , Neissseria spp.…”
Section: Discussionsupporting
confidence: 89%
“…The role of fungi in CRS is currently unclear. Culture-based studies have reported very low rates of isolation of fungi from CRS samples [20], [22], whereas the direct microscopic analysis of eosinophilic mucin in some cases detects fungi in 100% of patient samples [45]. In the patient cohort analysed here, CRS appeared to be of a non-fungal aetiology.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Hsu et al [24], Nadel et al [25], and Araujo et al [26] observed gram-negative microbes in 327 (26 %) infected patients, whereas Mantovani et al [23] observed gram-negative microbes in 58.6 % of infected patients. The predominant isolates in these studies were P. aeruginosa and H. influenzae.…”
Section: Discussionmentioning
confidence: 99%
“…To date, microbiota analysis of the nasal and sinus from CRS patients has been performed using standard lab techniques. S. epidermidis levels were found to be higher in controls when compared to CRS [16]. Upon comparison of ARS and CRS, there was a greater increase in the levels of gramnegative rods, S. aureus, and anaerobes in CRS [17][18][19][20][21][22][23][24][25].…”
Section: Crs Nasal and Sinus Microbiotamentioning
confidence: 99%